1972
DOI: 10.1364/ao.11.000345
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Measurements of X-Ray and Neutron Emission from Laser-Produced Plasmas

Abstract: Two Nd-glass laser systems have been assembled for producing high-temperature plasmas. The smaller laser, which gives subnanosecond pulses of about 5 J, has been used primarily for x-ray studies. The spectrum above 2 keV is being explored using Bragg reflection from a cylindrically curved graphite crystal. Line radiation appears to be present in the spectra measured for laser-produced plasmas of lead and gold. Plasma temperatures implied by x-ray transmission measurements are found to vary with absorber thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Further improvements in sensitivity (by about a factor of 5) may be obtained by utilizing pyrolytic graphite as the diffracting crystal (see Table 2). It is also possible to deposit pyrolytic graphite onto a cylindrical substrate and thus circumvent the problems of bending crystals to cylindrical shapes (Mead et al 1972).…”
Section: (B) Efficiency 0/ X-ray Production and Detectionmentioning
confidence: 99%
“…Further improvements in sensitivity (by about a factor of 5) may be obtained by utilizing pyrolytic graphite as the diffracting crystal (see Table 2). It is also possible to deposit pyrolytic graphite onto a cylindrical substrate and thus circumvent the problems of bending crystals to cylindrical shapes (Mead et al 1972).…”
Section: (B) Efficiency 0/ X-ray Production and Detectionmentioning
confidence: 99%
“…Focal spot size was determined by methods previously described. 105 The 20-psec structure and 1.2-A spectrum peri odicities observed in Figs. 88 and °0a, respectively, originate in the oscillator from a 3-mm-fhjck window in a Pockets cell used for Q.-switching.…”
Section: Recent Results With the Long Path Lasermentioning
confidence: 93%
“…In 1972, Mead et al 71 ) and found on the basis of time-of-flight measurements that the neutrons came from the target. However, based on their hydrodynamic predictions of just 10 -2 neutrons per shot and observations that the neutrons disappeared when a background gas was added, they concluded that the neutrons were not thermonuclear.…”
Section: A the Quest For Neutronsmentioning
confidence: 99%